FINITE ELEMENT ANALYSIS OF EMBANKMENTS ON SOFT CLAYS - CASE STUDIES (Journal of Engineering, 2009)
In order to design structures on soft soils, it is necessary to predict the behavior of the soft soilunder imposed structure load. The high excessive settlements of the soft soil can cause manyproblems for the structures built on the soil like cracking and breakup of pavements, railway,highway embankments, etc...In this work, the finite element method is utilized as a tool for carrying out differentanalyses of embankments on soft ground with different conditions. The computer program CRISP(CRItical State Program) is developed to suit the problem requirements. CRISP uses the finiteelement technique and allows predictions to be made of soil deformations using the critical statetheory.Eight-node isoparametric quadrilateral element has been added to the program. The programwas used to analyze fully coupled (Biot) consolidation of two-dimensional plane strain problems.The finite element predictions of displacements and excess pore water pressures were comparedwith field measurements.It was concluded that the maximum vertical movement occurs below the centerline of theembankment. The settlement decreases slightly as the toe of the embankment is approached anddecreases rapidly as the distance away from the toe increases. Upward movement of the surface farfrom the toe is observed. The maximum horizontal movement occurs near the top boundary. Therate of horizontal movement at the top of the foundation is greater than at the bottom. This behaviormay be due to the flexibility and free movement condition of the vertical boundary in the top half